(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Novel Coronavirus disease (COVID-19) is an infectious disease caused by a newly discovered coronavirus. Most people who fall sick with this disease will experience moderate symptoms and recover without any special treatment but those who are having respiratory and cardio diseases may affect the infections in a serious way. The infection was seen in Kerala by the end of February, by the end of March Kerala Government declared lockdown for keeping the people more safe. Lockdown was started for 7 days and government extended it to end of April 2020. Gradually the government give relaxation on lockdown. Different sectors were affected in this pandemic followed by lockdown. Migrants employees were inattentive group of people those who were belongs to less privileged category moved from different parts of the country for their livelihood ,movement of people from the place of birth to anywhere to reside and settle can be called as ‘migration’1. According to IOM2 “migration is the movement of a person or a group of persons either across an international boarder or within a country/state”. The process of migration is as old as human history as it pave the way for forming different civilizations and surely, it will continue till human life exists. This study tries to analyze how the migrants face the financial issues in the time of lockdown 2020, it also tries to find out the socio-economic background of the in-migrant workers. Thus to explore the reasons behind their migration to Kerala and their working atmosphere, heterogeneity among them in terms of place of origin, age groups, culture, educational standards, their consumption pattern, improvements in earnings, savings, living standards etc. Therefore this study stands relevant and timely in the light of above mentioned dimensions. The economic conditions of the migrant workers in Ernakulam district at the time of lockdown, sample collected was 134 migrants analysis of statistical data we use SPSS 22 version. Used Excel for graphical representation of the data,mainly carryout statistical test such as: Paired t test& Cross tabulation.Descriptive design with quantitative method is used.